The Mental Health of Medical Workers During the Covid19 Pandemic: How Do We Manage It? - Devi Arine Kusumawardani; Globila Nurika; Nurul Ulya Luthfiyana (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Covid-19 pandemic has occurred in many countries and caused a world health crisis. The morbidity dan mortality rate due to Covid-19 still rising until now. The outbreak of Covid-19 was not only affected the mental health of community but also affect the medical workers as the frontline. Therefore, we present an overview of the mental health outcomes in medical workers and describe the management at the organizational and personal level. Literature is obtained through searches from the ScienceDirect, PubMed, and Google Scholar databases which are further classified and summarized based on research questions. Discussion: The impact of the Covid-19 pandemic on the mental health of medical workers shows that the majority of workers experience anxiety, insomnia, depression to severe stress. The risk of mental disorders in women is higher than men, nurses are higher than doctors, and middle and junior positions are higher than senior degrees. Efforts that have been made in controlling mental health problems for workers in health services include periodic mental health monitoring, psychological support through self-care, mindfulness techniques, active listening, music therapy, internal counseling, and problem solving among ourselves. In addition, workers in health services must also get social support such as instrumental support to emotional support in the workplace. Conclusion: Medical workers in the health services have a very high risk of experiencing mental health problems during the Covid-19 pandemic so that the role of leaders in every health care facility is required in carrying out stress management activities in the workplace.